Three-phase boost-stage coupled current source inverter concept and its space vector modulation - Wang, Weiqi; Li, Xinian; Rui, Shuling; Xia, Xiaoting (Frontiers in Energy Research, 2023)
The current source inverter (CSI) is essentially a converter with inherent boost capability and has been preliminarily applied in the field of renewable energy generation systems. However, conventional CSIs are mostly operated independently. Several existing multilevel CSI topologies entirely rely on parallel combinations, which seems to be not very suitable for capacity expansion. To solve this issue, this paper proposes a concept of three-phase boost-stage coupled current source inverter (BSC-CSI) through the duality principle, which can output multi-level currents with a reduced number of switches as well as hardware costs. Compared with the state-of-the-art CSIs, the proposed BSC-CSI can notably simplify the implementation of the multi-level modulation scheme and meanwhile ensure the power devices switch under lower current stress. To further take full advantage of the modularity and scalability, the BSC-CSI can be constructed by hybrid using silicon-carbide (SiC) and silicon (Si) based semiconductor switches for improving efficiency. The experimental results have verified the theoretical findings.